The Influence of Safety Climate and Safety Leadership on Safety Behavior of Production Employees at PT. CF, Serang Regency - Prasetya, Ade Yoga; Abdullah, Syahfirin; Sembiring, Edison Cholia; Setyawati, Ekaterina (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In the industrial world, especially in fabrication industries, problems related to work and conditions triggering hazards and risks of workplace accidents can arise. Workplace accidents can be caused by two main factors, namely unsafe acts and unsafe conditions. Based on the preliminary study conducted by researchers on 15 production employees at PT. CF in Serang Regency, the results showed that 66.7% of employees have poor safety behavior. This study aims to determine the influence of safety climate and safety leadership on safety behavior among production employees at PT. CF in Serang Regency. The method used in this study is descriptive and associative methods with a quantitative research approach. The population of this study is all employees in the production department at PT. CF. The total number of production department employees is known to be 203 people. The sample size to be used in this study is 134.7 rounded to 135 employees in the production department at PT. CF. This study uses data analysis method with smart PLS software version 3.0 Partial Least Square (PLS) test. The results of the study show that there is an influence of safety climate on safety behavior among production employees at PT. CF in Serang Regency, as seen from the p-value of 0.002. There is an influence of safety behavior on safety behavior among production employees at PT. CF in Serang Regency, as seen from the p-value of 0.000.